Measured and estimated of constant and shuttle running in soccer players - Stevens, T. G. A.; De Ruiter, C. J.; Van Maurik, D.; Van Lierop, C. J. W.; Savelsbergh, G. J. P.; Beek, P. J. (Medicine & Science in Sports & Exercise, 2015)
Purpose: Players in team sports like soccer often make acceleration and deceleration movements, which are more energetically demanding than running at constant speed. The first aim of the present study was to estimate this difference in associated energy cost. To this end, we compared the actual energy cost of shuttle running to that of running at constant speed. In addition, since measuring oxygen consumption is not feasible during soccer, the study`s second aim was to determine the validity of an indirect approach to estimate energy cost provided by di Prampero et al. (2005) using time-motion data obtained from a tracking system as input.